Global trends in intergenerational income inequality? - Gabriele Guaitoli; Roberto Pancrazi (Luxembourg Income Study (LIS), 2022)
We document the evolution of intergenerational income (IGI ) inequality, measured as the relative income between old and young individuals, using harmonised microdata from 42 countries at different stages of economic development. In the last 20 years, IGI inequality has increased (in favour of the old) in all rich countries, while it fell or remained constant in lower-income countries. We show that these diverging trends are due to different channels. In rich countries, the main contributor to the increased IGI inequality is the divergence in employment rates between young and old. Instead, in lower-income countries, we observe a strong counteracting force driven by a faster increase in labor income, conditional on being employed, of the young with respect to the old. We propose some possible explanations for the observed stylized facts, focusing on the role played by long-run trends in economic fundamentals. We find that changes in the differential in education achievement and high-skill occupation employment between young and old are strongly connected to the changes in income intergenerational inequalities but in nonobvious ways. In high-income countries, old individuals are catching up with younger ones in educational achievement: this share shift can explain half of the rise of the IGI inequality in the last two decades. Instead, the faster shift of young workers into betterpaid occupations is at the centre of the fall of IGI inequality in lower-income countries, where it explains 40 percent of the average fall.
Keywords: E24; J31; O57; 330; Intergenerational inequality; income inequality; growth decomposition; cross-section; education gap; high-skilled occupation gap